Penerapan Pengambilan Keputusan Strategis pada Pesantren Udara 14.2690 MHz - Kurniawan, Luqman (STID Al Hadid Surabaya, 2023)
Every organization is required to make decisions in various forms to respond changes in circumstances and conditions so that organizational goals are achieved. Accuracy in making decisions will have an impact on organizational progress, especially for strategic decisions. Da'wah organizational strategic decisions are as important as other organizational strategic decisions. The Pesantren Udara 14.2690 MHz is a da’wah organization that preaches through amateur radio. In development there are several problems experienced internally and require organizational decisions, especially in the development of contemporary interpretation studies. This article aims to describe implementation of strategic decision making for the development of contemporary interpretation studies at the Pesantren Udara 14.2690 MHz. This research approach is descriptive qualitative. Data sourced from interviews, observations, and literature as support. The analysis process uses the theory of strategic decision making. The results: first, the strategic decision-making model is more appropriate for performing organizations, not start-up organizations, so adjustments are needed. Second, adjustments are needed in viewing the problems in the problem identification stage. Third, the development of alternative solutions/strategies doesn’t have to be linear or straight to the problem or negation of the problem, it needs to be adapted to the needs and conditions of the organization.